PENGARUH CITRA MEREK, KESADARAN MEREK, DAN PEMASARAN DIGITAL TERHADAP KEPUTUSAN PEMBELIAN AMDK AQUA - Dewi, Anak Agung Inta Setya; Indiani, Ni Luh Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
There are a number of bottled drinking water (AMDK) brands in the market, AQUA as a pioneer of AMDK has succeeded in becoming the market leader in the industry. This raises interest in analyzing the factors that drive AQUA to become AMDK market leader in Indonesia. This study aims to analyze the influence of brand image, brand awareness, and digital marketing on consumer’s decision to purchase AQUA in Denpasar. The population in this study is Denpasar citizens who have ever consumed bottled drinking water. The sample used was 100 people. Data was collected using survey method with a questionnaire. Multiple linear regression analysis technique was used to test the effect of independent variable on dependent variable. This study found that brand image and digital marketing have a positive and significant impact on purchase decision, but brand awareness has a positive and insignificant impact on purchase decision. To improve brand image, AQUA needs to have a distinctive character, unique and superior to its competitors. To improve the performance of the digital marketing aspect, AQUA needs to develop marketing in digital media, such as in its official website, social media, search engine, and implement affiliate marketing.